Strategies for the continuity of the historical city: the denied maintenance approach - Massimo Lauria; Maria Azzalin (Agathón)
Widening the concept of temporal continuity – which invokes the unavoidable changeover between fathers and sons – to the field of anthropic transformation, allows reflecting on the historical city and on the current regenerative changes concerning it. Among these, the maintenance approach that, today, even in an unlearning opportunity, could be an ecological and sustainable alternative to dominant technical culture. In this scene, the contribution argues the reasons for its reaffirmation, deepening its developmental dynamics: from renewed multiscale and multidisciplinary approaches to the main implemental tools.